2014
DOI: 10.1111/jicd.12122
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and Helicobacter pylori infection: a community‐based study using serology and rapid urease test

Abstract: Because periodontal disease is associated with the increased colonization of H. pylori, new treatment modalities, such as plaque control measures, should be employed for the complete management of H. pylori-associated gastric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
0
24
0
3
Order By: Relevance
“…H. pylori is a ubiquitous Gram-negative bacterium that infects about half of the world's population and is associated with peptic ulcers 67. The reported prevalence of H. pylori seropositivity in India is 50–77%, and its eradication may impact the morbidity experienced by PD patients 8. However, no supporting data are currently available from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori is a ubiquitous Gram-negative bacterium that infects about half of the world's population and is associated with peptic ulcers 67. The reported prevalence of H. pylori seropositivity in India is 50–77%, and its eradication may impact the morbidity experienced by PD patients 8. However, no supporting data are currently available from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated possible involvement of H. pylori in the pathogenesis of glossitis, halitosis, burning mouth syndrome, recurrent aphthous ulcerations and even periodontitis. 13 Detection of H.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse ethnical groups composed the studies and the patients were enrolled both in a Hospital-based population and a Community-based population [12,[24][25][26][33][34][35][36][37][38][39]. The studies used four types of diagnosis methods for H. pylori detection: Rapid Urease test (RUT) Serological test to antibody against the bacteria Polymerase Chain Reaction (PCR) and saliva H. pylori antigen test (HPS) [12,24,25,[33][34][35][37][38][39]. Tree studies focused in to assess the H. pylori infection as potential risk factor for periodontitis [12,24,33].…”
Section: Characteristics Of Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…Tree studies focused in to assess the H. pylori infection as potential risk factor for periodontitis [12,24,33]. On the other hand, eight studies were conducted to clarify the periodontitis as risk factor for H. pylori infection [25,26,[34][35][36][37][38][39]. All studies presented more than seven points in the score scale and were included in the results.…”
Section: Characteristics Of Studies Included In the Systematic Reviewmentioning
confidence: 99%